استخدام كسر الطابوق الطيني المعاد كبديل عن الحصى في انتاج بموك نمطي اقتصادي (Journal of Engineering, 2024)
During the last 5 decades, it is evident that there is a drastic need for close cooperation between the Iraqi architect and other engineers, technicians working with him, towards solving particular problems related to materials, system building technology in Iraq.The architect need to become a leader of the building team instead of becoming"a Hero". The research develop a light weight modular block (25x25x12.5cm), equivalent in volume to 3 bricks (25x12.5x7.5 cm). The proposed modular block use broken or crushed bricks as an aggregate instead of stone. The block can be handled easily, it can be produced mechanically 1.e. via compressors or manually. The research cover the use of recycled "broken or crushed" bricks by making samples, record photos and statistics. The samples uses 40-65% of the volume recycled bricks. The insulating factor increased up to 70-80% while cost decreased by approximately half. The paper is one of many applied research topics needed to be tackled on recycling, sustainability and environment improvement in Iraq